Acute chromatin decompaction stiffens the nucleus as revealed by nanopillar-induced nuclear deformation in cells - Aninda Mitra; Marie F. A. Cutiongco; Romina Burla; Yongpeng Zeng; Qin Na; Mengya Kong; Benjamin Vinod; Mui Hoon Nai; Barbara Hübner; Alexander Ludwig; Chwee Teck Lim; G. V. Shivashankar; et al. (Proceedings of the National Academy of Sciences, 2025)
Chromatin architecture is critical in determining nuclear mechanics. Most studies focus on the mechanical rigidity conferred by chromatin condensation from densely packed heterochromatin, but less is known on how transient chromatin decompaction impinge on nucleus stiffness. Here, we used an array of vertically aligned nanopillars to study nuclear deformability in situ after chromatin decompaction in cells. The nucleus significantly stiffened within 4 h of chromatin decompaction but softened at longer timescales. This acute stiffening of the nucleus was underpinned predominantly by an increase in nucleus volume and nuclear import, and partially by enhanced lamin protein recruitment to the periphery. The coupling between nucleus stiffening and acute chromatin decompaction was observed in low malignancy cancer cell lines (e.g. MCF7, PEO1, A549) but weakened in highly malignant counterparts (e.g. MDA-MB-231, HEYA8, HT1080) due to the capacity to efficiently compact heterochromatin into foci that sustains nucleus deformability required for confined migration. Our work signals how rapid chromatin remodeling is a physiologically relevant pathway to modulate nucleus mechanics and cell migration behavior.